Effects of Lipotoxicity in Brain Microvascular Endothelial Cells During Sirt3 Deficiency-Potential Role in Comorbid Alzheimer’s Disease - Tyagi, Alpna; Mirita, Carol; Shah, Iman; Reddy, P. Hemachandra; Pugazhenthi, Subbiah (Frontiers in Aging Neuroscience, 2021)
SIRT3 is a deacetylase enzyme that enhances the function of key mitochondrial proteins. We have earlier demonstrated that deletion of Sirt3 gene leads to downregulation of metabolic enzymes, mitochondrial dysfunction and neuroinflammation in the brain, the major causes of Alzheimer’s disease (AD). We also reported recently that Sirt3 gene deletion in Alzheimer’s transgenic mice leads to exacerbation of neuroinflammation, amyloid plaque deposition and microglial activation. AD often coexists with other brain lesions caused by comorbidities which can exert their deleterious effects through the neurovascular unit. This unit consists of brain microvascular endothelial cells (BMECs), end feet of astrocytes, and pericytes. BMECs are uniquely different from other vascular endothelial cells because they are glued together by tight-junction proteins. BMECs are in constant contact with circulating factors as they line the luminal side. Therefore, we hypothesized that vascular endothelial injury caused by comorbidities plays a significant role in neuroinflammation. Herein, we investigated the effects of lipotoxicity in BMECs and how Siirt3 deficiency facilitate the deleterious effects of lipotoxicity on them using in-vivo and in-vitro models. We observed decreases in the levels of SIRT3 and tight junction proteins in the brain samples of western diet-fed APP/PS1 mice. Similar observations were obtained with Alzheimer’s post-mortem samples. Exposure of BEND3 cells, a mouse BMEC cell line, to a combination of high glucose and palmitic acid resulted in significant (P<0.01-P<0.001) decreases in the levels of SIRT3, claudin-5 and ZO-1. Induction of inflammatory mediators, including Cox-2, CXCL1, RANTES and GADD45β was also observed in these treated cells. Interestingly, the induction was more with Sirt3-silenced BEND3 cells, suggesting that Sirt3 deficiency exacerbates inflammatory response. Palmitic acid was more potent in inducing the inflammatory mediators. Significant cytotoxicity and changes in microglial morphology were observed when cocultures of Sirt3-silenced BEND3 and Sirt3-silenced BV2 cells were exposed to palmitic acid. Transendothelial electrical resistance measurement with these cocultures suggested decreased barrier integrity. The findings of this study suggest that hyperlipidemia in comorbities can compromise blood brain barrier integrity by inducing inflammatory mediators and decreasing tight junction proteins in the vascular endothelial cells of the AD brain, leading to activation of microglia.